Effect of the Interaction between Audit Firm Size and Audit Quality on the Financial Performance of Listed Consumer Goods Companies in Nigeria - Taophic Olarewaju Bakare (Universitas Syiah Kuala, 2022)
Objective – The main objective of this study is to examine the effect of the interaction between audit firm size and audit quality on the financial performance of listed consumer goods companies in Nigeria.Design/methodology – The sample used in this study are seventeen (17) listed consumer goods companies that merit the sampling techniques of the study for the period 2010-2020. The study used the GMM estimator techniques of data analysis.Results – The results revealed that interaction of audit firm size and ACFE, and board size have positive and significant effect on the net profit margin as proxy for financial performance of listed consumer goods companies.Research Limitations/Implications – The study is limited to consumer goods industries on Nigerian exchange group. Implication of this study is that it will improve the understanding of audit firm size and audit quality concept in practice at all levels of organization especially in the consumer goods companies’ environment where auditors and regulators when assessing the appropriateness of accounting policy choices, interest of stakeholders is highly consider. And thereby recommends that ethical standard should be encouraged by the regulatory agencies if not mandated as this will lead to improvement of audit quality.Novelty/Originality – The originality of this research lies in the methodology of the study where previous studies only analyzed the data through standard econometric techniques such as OLS which do not provide unbiased estimates, due to the presence of the lagged dependent variable among the explanatory variables in which Generalized Method of Moments (GMM) used by this study addressed those issues. That makes this study a unique one and contribution to the body of knowledge